2021
DOI: 10.1002/joc.7145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of future meteorological drought hotspots over Indian region: A study based on NEX‐GDDP data

Abstract: The present study aims to answer the following two research questions using the future outputs from 19 GCMs of the novel NASA Earth Exchange Global Daily Downscaled Projections (NEX‐GDDP) under two Representative Concentration Pathway (RCP) 4.5 and 8.5 scenarios. (a) What will be the possible variability of future meteorological drought properties during the 21st century? (b) What will be the possible influence of temperature in modulating the drought properties? In order to answer the above questions, five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 66 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…By engaging temperature and precipitation data, Ali et al (2021) identified climate change hotspots in terms of extremes by executing a comparative analysis of local cities with sub-regional rate of change in future at annual and seasonal scales. Das et al (2021) engaged five properties namely frequency, severity, duration, peak, and areal spread of drought indices to analyze climate change hotspots in future projections. Also very recently, researchers identified thermal hotspots through heat index determination and urban heat island mitigation using a numerical microclimate model for their area of study (Perera et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…By engaging temperature and precipitation data, Ali et al (2021) identified climate change hotspots in terms of extremes by executing a comparative analysis of local cities with sub-regional rate of change in future at annual and seasonal scales. Das et al (2021) engaged five properties namely frequency, severity, duration, peak, and areal spread of drought indices to analyze climate change hotspots in future projections. Also very recently, researchers identified thermal hotspots through heat index determination and urban heat island mitigation using a numerical microclimate model for their area of study (Perera et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…(2009). Moreover, in past, the same datasets have been used to analyse different extreme events in India (Murari et al ., 2015; Rohini et al ., 2016, 2019; Sharma and Goyal, 2018; Jha et al ., 2019; Das et al ., 2020a, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Quality control has been performed to develop the dataset and the details can be obtained in Srivastava et al (2009). Moreover, in past, the same datasets have been used to analyse different extreme events in India (Murari et al, 2015;Rohini et al, 2016Rohini et al, , 2019Sharma and Goyal, 2018;Jha et al, 2019;Das et al, 2020aDas et al, , 2021.…”
Section: Observed and Future Datasets Of Tmaxmentioning
confidence: 99%
“…There are many methods/indexes, such as Standardized Precipitation Index (SPI) (Bayat et al, 2015), Rainfall Departure Analysis (Kumar et al, 2020), Standardized Precipitation-Evapotranspiration Index (SPEI) (Das et al, 2021) and so on, have been used to identify the prolonged meteorological drought. Saft et al (2015) introduced a drought definition algorithm that was based on the annual rainfall only, and has been proved to have lower degree of dependence and the stronger robustness than other selected approach in the south-eastern Australia catchments.…”
Section: Identification Of Prolonged Meteorological Droughtmentioning
confidence: 99%